Management of dentoalveolar fracture by using rigid wire and composite splint: A case report - Firstyananda W; Sjamsudin E (DiscoverSys Inc., 2018)
Introduction: Dentoalveolar fractures in adults often occur in the context of daily activities and traffic accidents. Crown fracture is the most common type of lesion, followed by tooth mobility.Case: A 67-year-old woman came to the Emergency Department with bleeding from the mouth because she fells down and her lips hit the bathroom floor. There was no history of unconsciousness, vomiting, and bleeding from ear and nose. The extraoral examination found an asymmetrical face, hematoma on the right eye area, nasolabial region and chin. Edema and hematoma on the upper and lower lip. The intraoral examination was found generalized hyperemia gingiva. The diagnosis was dentoalveolar fracture 12, 22 with crown fracture of teeth 11, 21, 22 accompanied by mobility grade 2 of 12, 11. First treatments are wound debridement, splinting with rigid wire and composite splint, and selective grinding. Panoramic references and prescribing antibiotics and analgesics. Post-action instructions include maintaining oral hygiene, soft diet, radices removal, and return for splinting control. Treatment results show good soft and hard tissue healing. Conclusion: Rigid wire and composite splint are one of the most common and easy fixation techniques to treat dentoalveolar fractures. Simple tools and techniques make rigid wire and composite splint a good treatment for simple dentoalveolar fractures.